Frost formation modeling during the storage of frozen vegetables exposed to temperature fluctuations. (December 2017) - Urquiola, A.; Alvarez, G.; Flick, D.
Abstract: The quality of frozen vegetables is affected by temperature fluctuations during storage, when weight loss and frost formation are generally observed. In order to predict frost formation during storage of frozen vegetables, a numerical model consisting of a cylindrical container filled with frozen carrot slices was developed. It was exposed to external temperature fluctuations. The parameters of the model were identified by experimental measurements or found in the literature. The model was validated using a set of independent experimental results that showed good agreement with the simulated predictions. The model is able to predict air velocities, air and product temperatures and local frost formation. It was used to show that the most important parameters affecting total frost formation are the effective mass diffusivity and the convective heat coefficient within the container. Highlights: A numerical model was developed to predict local temperature and frost formation in bulk frozen products (porous media), subjected to temperature fluctuations. Parameters of the model were identified by a minimum of simple tests. The model was validate experimentally, and simulations show the most susceptible regions to frost formation.